Paleoceanography and paleoclimate in the Nordic Seas and the northern North Atlantic during the last 22 000 years - Meland, Marius Yddal (Quaternary Science Reviews, 2006)
The paleoceanography of the Nordic Seas and the northern North Atlantic during glacial and deglacial times was studied, using oxygen isotopes and Mg/Ca of foraminifera. The specific objectives are listed below: 1) Sea surface temperatures (SST) during the Last Glacial Maximum (LGM, ∼20 000 years ago) were reconstructed, using oxygen isotopes of the planktonic foraminifer Neogloboquadrina pachyderma (sinistral). 2) The LGM climate (air temperatures, precipitation/moisture, air pressure, wind systems) was simulated, using the SSTs produced under Objective 1 as boundary conditions. 3) Mg/Ca ratios of N. pachyderma (sin.) were tested to see if they could be used to make surface/subsurface temperature estimates in the Nordic Seas for previous times. 4) Water mass exchanges between the North Atlantic and the Nordic Seas through the period 22 000 - 6000 years ago were studied. This period covers the LGM, the last deglaciation and the recent interglacial (Holocene). Benthic oxygen isotopes were used as the main proxy, supported by benthic carbon isotopes and planktonic oxygen isotopes.